Coronavirus disease-2019: knowledge and practices behaviour of healthcare workers at a university teaching hospital in Malaysia - Lee, Kai Wei; Yusof Khan, Abdul Hanif Khan; Ching, Siew Mooi; Devaraj, Navin Kumar; Baharin, Janudin; Chia, Peck Kee; Loh, Wei Chao; Abdul Rashid, Anna Misya'il; Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Mohd Noor, Mohd Tawfeq; Sivaratnam, Dhashani; et al. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Coronavirus disease-2019 (COVID-19) was declared a global pandemic in March 2020, with 15 million people have been infected worldwide, and this number is increasing. Our study sought to assess the knowledge and practice of healthcare workers (HCWs) in a teaching hospital in Malaysia. Methods: This cross-sectional study was undertaken using online Google form links among HCWs. Knowledge and practice were assessed using a validated questionnaire. The analysis was performed with SPSS version 26. Factors associated with poor knowledge were analysed using multivariate analysis. Results: A total of 193 HCW responded to our online survey. Majority of our HCWs were female (74.1%) with a mean age of 32.5 years. We found 53 (27.5%) and 134 (69.4%) of our HCWs had good knowledge and good practice on COVID-19, respectively. Knowledge gap was identified in the symptomatology, investigation methods and management. Based on multiple logistic regression, determinants of poor knowledge scores were those work as medical attendants (aOR = 3.626; 95% CI = 1.489, 8.834) and nurses (aOR = 4.107; 95% CI = 1.175, 14.358). Conclusion: Around one-third and 70% of our HCWs have good knowledge and practice of COVID-19 infection respectively. Continuous, specifically targeted and updated medical education, need to be carried out to improve the knowledge and practice among our HCWs in order to keep abreast of the fast-moving pace of COVID-19 knowledge development.